Extraction and preconcentration of residual solvents in pharmaceuticals using dynamic headspace–liquid phase microextraction and their determination by gas chromatography–flame ionization detection. (10th August 2016) - Farajzadeh, Mir Ali; Dehghani, Hamideh; Yadeghari, Adeleh; Khoshmaram, Leila
Abstract: The present study describes a microextraction and determination method for analyzing residual solvents in pharmaceutical products using dynamic headspace–liquid phase microextraction technique followed by gas chromatography–flame ionization detection. In this method dimethyl sulfoxide (μL level) placed into a GC liner‐shaped extraction vessel is used as a collection/extraction solvent. Then the liner is exposed to the headspace of a vial containing the sample solution. The effect of different parameters influencing the microextraction procedure including collection/extraction solvent type and its volume, ionic strength, extraction time, extraction temperature and concentration of NaOH solution used in dissolving the studied pharmaceuticals are investigated and optimized. Under the optimum extraction conditions, the method showed wide linear ranges between 0.5 and 5000 mg L −1 . The other analytical parameters were obtained in the following ranges: enrichment factors 240–327, extraction recoveries 72–98% and limits of detection 0.1–0.8 mg L −1 in solution and 0.6–3.2 μg g −1 in solid. Relative standard deviations for the extraction of 100 mg L −1 of each analyte were obtained in the ranges of 4–7 and 5–8% for intra‐ day ( n =  6) and inter‐ day ( n =  4) respectively. Finally the target analytes were determined in different samples such as erythromycin, azithromycin, cefalexin, amoxicillin and co‐amoxiclav by the proposed method.